A Zn-MOF@Co 2+ Preparation method and application of derivative materials

By using Zn-MOF@Co2+ derivative material as an electrocatalyst, the problem of insufficient selectivity, activity and stability of H2O2 synthesis in the prior art was solved, and an efficient and low-cost electrocatalytic synthesis effect was achieved.

CN115216790BActive Publication Date: 2025-05-02ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210946338.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-08
Publication Date
2025-05-02
Estimated Expiration
2042-08-08

AI Technical Summary

Technical Problem

In the prior art, when using precious metal-based electrocatalysts, it is difficult to improve the selectivity, activity and stability of hydrogen peroxide (H2O2) synthesis, and the high cost and scarcity of precious metal catalysts hinder widespread application.

Method used

Zn-MOF@Co2+ derivative material was used as an electrocatalyst to construct Zn-MOF through zinc source and organic ligand, and cobalt ions were adsorbed by physical mixing, and finally calcined under a protective atmosphere to obtain the Co@mC composite material. The material has a high specific surface area and porosity, and has excellent electrocatalytic properties when used as an electrocatalyst.

Benefits of technology

The selectivity, activity and stability of H2O2 synthesis are improved, the cost of electrocatalytic synthesis of H2O2 is reduced, and the high conductivity and defect sites of the material promote electron transfer and improve electrocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115216790B_ABST
    Figure CN115216790B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of nanomaterials, and specifically relates to a preparation method and application of a Zn-MOF@Co 2+ derived material. The preparation method of the Zn-MOF@Co 2+ derived material of the present invention comprises the following steps: 1) Reacting a zinc source and an organic ligand in a solvent, performing solid-liquid separation, and drying the solid to obtain Zn-MOF; 2) Stirring and mixing a cobalt salt and Zn-MOF in an organic solvent, performing solid-liquid separation, and drying the solid to obtain Zn-MOF@Co 2+ ; 3) Calcining Zn-MOF@Co 2+ at 500°C to 900°C under a protective atmosphere to obtain the Zn-MOF@Co 2+ derived material Co@mC. The Zn-MOF@Co 2+ derived material of the present invention has a high specific surface area and porosity, excellent electrocatalytic performance, can be used as a catalyst for preparing H2O2, and improves the selectivity, activity and stability of H2O2 synthesis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanomaterials and specifically relates to a Zn-MOF@Co 2+ Preparation method and application of derivative materials. Background Art

[0002] Hydrogen peroxide (H2O2) is a green and benign oxidant widely used in anticancer therapy, antibacterial and wastewater treatment. Conventionally, H2O2 is produced by a large-scale indirect anthraquinone process, which has multiple redox reaction steps and requires noble metal-based catalysts. Currently, the electrochemical reduction of oxygen (2e - ORR) has attracted extensive research interest in the preparation of H2O2. However, inevitable side reactions (such as the formation of H2O) reduce the selectivity of H2O2 synthesis. To date, the most widely used noble metal-based electrocatalysts can achieve large-scale electrocatalytic synthesis of H2O2, but the high cost and scarcity of these noble metal catalysts have greatly hindered widespread adoption.

[0003] In recent years, various nanocatalysts such as carbon materials, single atoms (SACs), transition metal oxides (TMOs), and metal-organic frameworks (MOFs) have been explored to drive 2e - ORR to effectively produce H2O2. Among them, TMO has abundant reserves and is a potential ORR catalyst with excellent performance. However, their poor electrical conductivity restricts the further improvement of catalytic performance. The composite of TMO and carbon materials is a commonly used and particularly effective method in current modification technology. This composite material can effectively combine the advantages of both, greatly improving its electrochemical performance. For example, Zhang et al. (Zhang Y., Wang D., Wang X., et al. The influence of mesopore size distributions on the electrochemical activity and two-electron selectivity of the oxygen reduction reaction innitrogen-doped and CoOx-loaded activated carbon [J]. Journal of Electroanalytical Chemistry, 2019, 847: 113258.) used nitrogen doping and cobalt oxide loading to modify mesopore size distribution activated carbon (AC-2, 5-15nm). As an ORR catalyst, AC-2 forms CoO-loaded graphite N. The modified AC-2 has a very high tendency to 2e -The ORR pathway. In addition, a low-cost and high-efficiency rolled activated carbon electrode was prepared using the modified AC-2. The H2O2 electrosynthesis rate of RACE was 0.236±0.025mg / h / mA / cm 2 , the current efficiency is 63.25±6.79%, however, the preparation process of this method is complicated and difficult to achieve industrial production.

[0004] Our research group has conducted a long-term study on MOF materials. For example, China's invention patent CN 114288406A discloses a Zn-MOF@Ti3C2Tx hybrid material and its application in the field of antibacterial. However, how to use MOF materials for the efficient preparation of hydrogen peroxide requires further research. There is currently no report on the efficient use of MOF materials for electrocatalytic synthesis of hydrogen peroxide. How to improve the electrocatalytic ability of MOF materials and thus improve the production capacity of electrocatalytic hydrogen peroxide is still a problem that needs to be improved and studied. Summary of the invention

[0005] The purpose of the present invention is to provide a Zn-MOF@Co 2+ Preparation method of derivative materials, Zn-MOF@Co prepared by the method 2+ The derived materials have high specific surface area and porosity and exhibit excellent electrocatalytic performance when used as electrocatalysts.

[0006] The second object of the present invention is to provide a Zn-MOF@Co prepared by the above preparation method. 2+ The application of the derivative materials as catalysts for the electrocatalytic synthesis of hydrogen peroxide can improve the selectivity, activity and stability of H2O2 synthesis.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A Zn-MOF@Co 2+ The method for preparing the derivative material comprises the following steps:

[0009] 1) reacting the zinc source and the organic ligand in a solvent, separating the solid and the liquid, and drying the solid to obtain Zn-MOF;

[0010] 2) Mix the cobalt salt and Zn-MOF in an organic solvent, separate the solid and the liquid, and dry the solid to obtain Zn-MOF@Co 2+ ;

[0011] 3) Put Zn-MOF@Co 2+ Calcination at 500℃~900℃ under protective atmosphere to obtain Zn-MOF@Co 2+ Derivative material Co@mC.

[0012] Zn-MOF@Co of the present invention 2+ The preparation method of the derivative material first uses a zinc source and an organic ligand to construct a precursor Zn-MOF, and then adsorbs cobalt ions through physical mixing to obtain Zn-MOF@Co 2+ Finally, calcination was performed to obtain Zn-MOF@Co 2+ Derivative material Co@mC. After calcination, Co@mC is a stacked columnar structure with mesoporous and microporous structures and a large specific surface area, which can provide an intermediate transmission channel for electron transfer; Zn-MOF and Co(NO3)2 are converted into graphite carbon and CoO respectively after calcination, and CoO nanoparticles are evenly distributed in the graphite carbon skeleton. The high conductivity and defect sites of the graphite carbon skeleton can promote the transfer of electrons in the electrocatalytic process and improve the electrocatalytic performance of the Co@mC composite material.

[0013] Preferably, in step 1), the zinc source is zinc acetate dihydrate, and the organic ligand is curcumin; the mass ratio of the zinc source to the ligand is 6:10 to 12:10.

[0014] Preferably, the reaction in step 1) is first carried out at room temperature for 4 to 5 hours, and then heated to 60 to 90° C. for 48 to 96 hours.

[0015] In order to promote the formation of Zn-MOF materials, preferably, the solvent in step 1) is a mixed solvent of dimethylacetamide and anhydrous ethanol; the volume ratio of dimethylacetamide to anhydrous ethanol is 3:1 to 5:1.

[0016] Preferably, in step 2), the cobalt salt is cobalt nitrate hexahydrate; and the mass ratio of the cobalt salt to Zn-MOF is 1:2.

[0017] Preferably, in step 2), the organic solvent is methanol; the mixing is mixing the methanol solution of Zn-MOF with the methanol solution of cobalt nitrate hexahydrate, wherein the content of Zn-MOF in the methanol solution of Zn-MOF is 5 mg mL -1 The content of cobalt nitrate hexahydrate in the methanol solution of cobalt nitrate hexahydrate is 10 mg mL -1 .

[0018] Preferably, in step 2), the stirring is carried out at room temperature for 6 hours.

[0019] Preferably, in step 3), the calcination temperature is 900°C.

[0020] When the calcination temperature is 900℃, the volatilization of Zn promotes the formation of microporous structure inside the Co@mC composite material, which can bring a large number of defect sites and increase the specific surface area of ​​the Co@mC composite material; and the volatilization of Zn can effectively inhibit the aggregation of CoO nanoparticles, so that the CoO nanoparticles are evenly distributed in the graphite carbon skeleton, which is beneficial to improve the electrocatalytic performance of the Co@mC composite material.

[0021] Preferably, in step 3), the calcination time is 2 hours.

[0022] A Zn-MOF@Co prepared by the above preparation method 2+ Application of the derived materials as catalysts for electrocatalytic synthesis of hydrogen peroxide.

[0023] The Zn-MOF@Co prepared by the above preparation method 2+ The derived material has high specific surface area, porosity and abundant active sites, so the Zn-MOF@Co 2+ The derived materials can be used as catalysts for the electrocatalytic synthesis of hydrogen peroxide to efficiently prepare H2O2, and can improve the selectivity, activity and stability of H2O2 synthesis. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Zn-MOF@Co 2+ XRD patterns, Raman spectra, pore size distribution and XPS full spectra of related materials, among which (a) is Zn-MOF@Co 2+ , Co@mC-500, Co@mC-700, Co@mC-900, (b) is the Raman spectra of Co@mC-500, Co@mC-700 and Co@mC-900, (c) is the N2 adsorption / desorption isotherms (pore size distribution) of Co@mC-500, Co@mC-700, Co@mC-900, (d) is the Zn-MOF, Zn-MOF@Co 2+ , XPS full spectra of Co@mC-500, Co@mC-700 and Co@mC-900;

[0025] Figure 2 Zn-MOF@Co 2+ SEM images, TEM images and TEM element mapping images of Zn-MOF@Co 2+ SEM images of Zn-MOF@Co 2+ TEM image of Zn-MOF@Co 2+ TEM element mapping;

[0026] Figure 3SEM images of Co@mC composites, where (a, b) are SEM images of Co@mC-500 composites, (c, d) are SEM images of Co@mC-700 composites, and (e, f) are SEM images of Co@mC-900 composites;

[0027] Figure 4 TEM images, HR-TEM images and EDS mapping images of Co@mC composite materials, wherein (a, b, c) are TEM images, HR-TEM images and EDS mapping images of Co@mC-500 composite materials, (d, e, f) are TEM images, HR-TEM images and EDS mapping images of Co@mC-700 composite materials, and (g, h, i) are TEM images, HR-TEM images and EDS mapping images of Co@mC-900 composite materials;

[0028] Figure 5 Electrochemical characterization of Co@mC composite materials, where (a) is Zn-MOF, Zn-MOF@Co 2+ , Co@mC-500, Co@mC-700 and Co@mC-900 in O2-saturated 0.1 M KOH solution at a scan rate of 50 mV s -1 CV curves of (a) and (b) based on Zn-MOF and Zn-MOF@Co 2+ LSV curves of RRDE electrodes based on Zn-MOF, Zn-MOF@Co@mC-500, Co@mC-700 and Co@mC-900 composites in O2-saturated 0.1M KOH solution at 1600rpm. (c) 2+ , Co@mC-500, Co@mC-700 and Co@mC-900 composites, (d) the electron transfer number of RRDE electrodes based on Zn-MOF, Zn-MOF@Co 2 + , H2O2 selectivity of RRDE electrodes of Co@mC-500, Co@mC-700 and Co@mC-900 composites;

[0029] Figure 6 The catalytic activity of Co@mC composite materials is characterized, where (a) is Zn-MOF, Zn-MOF@Co 2+ , Co@mC-500, Co@mC-700 and Co@mC-900 composites at 0 V, 0.2 V, 0.4 V, 0.6 V, 0.8 V and 1.0 V vs. RHE (insert), (b) Zn-MOF, Zn-MOF@Co 2+, Tafel plots of Co@mC-500, Co@mC-700 and Co@mC-900 composites;

[0030] Figure 7 Polarization curves and related KL lines of Co@mC-900 composite materials, where (a) is the polarization curve of the RDE electrode based on the Co@mC-900 composite material at a rotation speed of 400 rpm-2025 rpm, and (b) is the related KL line of the polarization curve of the RDE electrode based on the Co@mC-900 composite material;

[0031] Figure 8 Co@mC-900 composite material and LSV curve and H2O2 selectivity test, where (a) is the LSV curve of the RRDE electrode based on Co@mC-900 composite material in O2-saturated 0.1M KOH solution at 1600rpm, (b) is the H2O2 selectivity test under different Co@mC-900 composite material loads;

[0032] Fig. 9 Static test of Co@mC-900, where (a) is the CV curve of Co@mC-900 after different cycles in O2-saturated 0.1M KOH, and (b) is the LSV curve of Co@mC-900 after different cycles in O2-saturated 0.1M KOH at 1600rpm;

[0033] Fig.10 Figure 1 is the stability test of Co@mC-900, where (a) is the chronoamperometric curve of the RRDE electrode (disk potential of 0.5 V, ring potential of 0.5 V) based on the Co@mC-900 composite material before and after the 10h stability test in O2-saturated 0.1M KOH, (b) is the LSV curve of the RRDE electrode based on the Co@mC-900 composite material in O2-saturated 0.1M KOH solution at 1600rpm, (c) is the selectivity test of the RRDE electrode based on the Co@mC-900 composite material for synthesizing H2O2, and (d) is the electron transfer number of the RRDE electrode based on the Co@mC-900 composite material;

[0034] Fig.11 The yield and Faradaic efficiency of H2O2 of the prepared Co@mC-900 catalyst at potentials of 0.2V, 0.3V, 0.4V, 0.5V and 0.6V in a practical device. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific implementation methods.

[0036] 1. Zn-MOF@Co of the present invention2+ Embodiment of the method for preparing the derivative material

[0037] Example 1

[0038] The Zn-MOF@Co 2+ The method for preparing the derivative material specifically comprises the following steps:

[0039] 1) Curcumin (600 mg) and zinc acetate dihydrate (540 mg) were added to a mixed solvent of dimethylacetamide (40 mL) and anhydrous ethanol (10 mL). After stirring at room temperature for 4 h, the solution was heated in a pressure bottle in an oil bath at 75 °C for 72 h; finally, the resulting suspension was centrifuged and washed with DMF several times, and then vacuum dried at 60 °C overnight to obtain Zn-MOF.

[0040] 2) Zn-MOF (100 mg) was uniformly dispersed in 20 mL of methanol by ultrasonic treatment. 20 mL of Co(NO3)2·6H2O (10 mg mL -1 ) methanol solution was slowly added to the above dispersion system and stirred at room temperature for 6 h. The resulting precipitate was collected by centrifugation, washed and dried in a vacuum oven for 12 h to obtain Zn-MOF@Co 2+ .

[0041] 3) Take 100 mg Zn-MOF@Co 2+ Place in a porcelain boat and calcine in a constant temperature tube furnace under nitrogen atmosphere. The heating rate during the calcination process is 5℃min -1 , heated to 500℃ and maintained at this temperature for 2h. After calcination, cooled to room temperature and taken out. After washing with 0.1M HCl and deionized water, dried under vacuum at 60℃ overnight, Zn-MOF@Co 2+ The derivative material was named Co@mC-500.

[0042] Example 2

[0043] The Zn-MOF@Co 2+ The preparation method of the derivative material is different from the method of Example 1 in that in step 3), the calcination temperature is 700°C. Finally, Zn-MOF@Co 2+ The derivative material was named Co@mC-700.

[0044] Example 3

[0045] The Zn-MOF@Co 2+ The preparation method of the derivative material is different from the method of Example 1 in that: in step 3), the calcination temperature is 900°C. Finally, Zn-MOF@Co 2+The derivative material was named Co@mC-900.

[0046] 2. Experimental Examples

[0047] Experimental Example 1: Structural Characterization of Materials

[0048] 1) Chemical structure of the material

[0049] Figure 1 (a) shows the Zn-MOF@Co 2+ From the XRD spectra of the calcined derivative materials, it can be seen that after calcination, the diffraction peaks of Co@mC-500 and Co@mC-700 at 31.7°, 34.3°, 36.2°, 47.5°, 56.5°, 62.8°, and 67.8° belong to the hexagonal wurtzite phase of ZnO, corresponding to the (100), (002), (101), (102), (110), (103), and (200) diffraction planes, respectively (JCPDS No.36-1451). This finding indicates that the Zn element is present in Zn-MOF@Co 2+ The ZnO was oxidized during the annealing process. Co@mC-900 did not show the relevant diffraction peaks of ZnO because of the volatilization of zinc during the high temperature treatment at 900℃, but the diffraction peaks corresponding to the (111), (200) and (220) diffraction planes of CoO at 36.5°, 42.5° and 61.5° can be observed (JCPDS No.48-1719). In addition, the weak diffraction peaks at 42.5° of Co@mC-500 and Co@mC-700 composite materials also indicate that they contain a small amount of CoO.

[0050] like Figure 1 (b) shows the Raman spectra of the Co@mC series at 1340 cm -1 and 1590cm -1 The disordered carbon peak (D band) and graphite carbon peak (G band) are shown in Fig. D / I G ) indicates the degree of defects in the graphite structure. The I D / I G The values ​​are 0.808, 1.025 and 1.217 respectively. D / I G The increase in value indicates that sp 3 Key to sp 2The conversion of bonds and the degree of defects in the MOF-derived carbon structure increase with the increase of calcination temperature. During the calcination process, Zn-MOF and Co(NO3)2 are converted into graphite carbon and CoO, respectively, and CoO nanoparticles are evenly distributed in the graphite carbon skeleton; as the temperature increases to 900℃, the volatilization of zinc brings a large number of defects. The high conductivity and defect sites of the graphite carbon skeleton can promote the transfer of electrons in the electrocatalytic process and improve the performance of electrocatalytic H2O2 production.

[0051] 2) Pore structure of the material

[0052] The pore structures of Co@mC-500, Co@mC-700 and Co@mC-900 were analyzed using N2 adsorption / desorption isotherms. Figure 1 (c) As shown. Co@mC-900 exhibits a type I isothermal adsorption-desorption curve, while Co@mC-500 and Co@mC-700 samples show typical type IV isothermal adsorption-desorption curves with obvious H3-type hysteresis loops, which reveals that the former is microporous in nature and the latter is a mesoporous structure. The specific surface areas of Co@mC-500, Co@mC-700 and Co@mC-900 are 446.97 m 2 g -1 、675.05m 2 g -1 and 720.53m 2 g -1 The pore size distribution of all samples shows both mesopore and micropore sizes, which are beneficial for O2 adsorption and H2O2 transport. It can be found that Co@mC-900 has the largest specific surface area and microporous structure, which is beneficial for 2e - ORR catalytic performance.

[0053] 3) Material composition analysis

[0054] Zn-MOF, Zn-MOF@Co 2+ The XPS spectra of Co@mC-500, Co@mC-700 and Co@mC-900 composites are shown in Figure 2. Figure 1 (d), where C1s and O1s signals coexist. It can be found that there are Zn 2p signals in the full XPS spectra of Co@mC-500 and Co@mC-700 composites, which should come from Zn-MOF@Co 2+ The ZnO component formed during the annealing process, but not in Co@mC-900, indicates that the Zn component volatilizes at a high temperature of 900 °C. Obviously, for the preparation of the Co@mC series, the peak intensity of the XPS signal of Zn 2p decreases with the increase of calcination temperature, which is consistent with the gradual decrease of Zn content. 2+Co 2p signals can be found in the series of Co@mC composites, indicating the successful doping of Co element. Since the calcination process of Co@mC composites is carried out in N2 atmosphere, obvious N1s signals can be observed in the series of Co@mC composites. N doping of the obtained Co@mC composites helps to improve the electrocatalytic performance of ORR.

[0055] Experimental Example 2: Surface morphology analysis of materials

[0056] 1) Zn-MOF@Co 2+ Analysis of the surface morphology

[0057] like Figure 2 (a, b) Zn-MOF@Co 2+ As shown in the SEM images, Zn-MOF@Co 2+ It is a columnar structure stacked layer by layer. Figure 2 (c, d) Zn-MOF@Co 2+ In the TEM image, nanoparticles can be seen, which may be attributed to the oxides generated by the oxidation of Zn and Co in air during the reaction, and it can also indicate that a large amount of Co 2+ was adsorbed into the pores of Zn-MOF, which was also confirmed by TEM elemental mapping. Figure 2 (e) is Zn-MOF@Co 2+ TEM element mapping, it can be seen that C, O, N, Co and Zn elements are evenly distributed in the selected area.

[0058] 2) Surface morphology analysis of Co@mC composites

[0059] Figure 3 The SEM images of Co@mC-500, Co@mC-700 and Co@mC-900 composites are shown. It can be seen that the Co@mC composites and Zn-MOF@Co 2+ By comparison, it can be seen that with the increase of calcination temperature, the porosity of Co@mC composite material increases, Co@mC-900 composite material shows abundant pores in nanorods, and the interlayer spacing of nanosheets also increases significantly, which may be attributed to the defects brought by ZnO after high temperature volatilization, which will help to improve the 2e - Electrocatalytic performance for ORR.

[0060] 3) Structure and elemental composition of Co@mC composites

[0061] The structure and elemental composition of the Co@mC composites were further determined by using TEM and EDS mapping images. Figure 4The carbon skeleton of the Co@mC composite is wrapped with uniformly distributed nanosheets, among which no obvious large nanoparticles are found in the high-magnification TEM. This result shows that the carbon network derived from Zn-MOF can effectively hinder the aggregation of metal clusters. Figure 4 (b, e, h). In the Co@mC-500 and Co@mC-700 composite materials, lattice fringes of 0.202 nm belonging to the (101) plane of the ZnO crystal can be observed. In the Co@mC-700 and Co@mC-900 composite materials, lattice fringes of 0.332 nm belonging to the (220) plane of the CoO crystal can be observed, which is consistent with the XRD results. The EDS spectra of all composite materials are shown in Figure 4 As shown in (c, f, i), C, N, O and Co elements are evenly distributed in the nanorods, and Co@mC-500 and Co@mC-700 contain a small amount of Zn element. By comparison, it was found that the CoO particles aggregated most seriously when the calcination temperature was 700°C. Generally, metal oxide particles will aggregate into larger clusters as the calcination temperature increases. The reason for the different phenomena here may be attributed to the fact that under the high-temperature calcination environment of 500 and 700°C, the presence of ZnO will cause CoO to aggregate and grow into nodules, which is most serious at 700°C. However, as the calcination temperature reaches 900°C, the volatilization of ZnO can effectively inhibit the aggregation of CoO nanoparticles. Figure 4 (i) It can be found that the Co element distribution in Co@mC-900 is the most uniform, indicating that the formed CoO nanoparticles are uniform in size and uniformly loaded on the Zn-MOF-derived carbon skeleton, which will be beneficial for the material to show excellent catalytic performance.

[0062] Experimental Example 3: Electrochemical Performance Test of Materials

[0063] All electrochemical measurements were performed in an electrochemical glass cell using a three-electrode system, with a platinum electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, and a glassy carbon electrode formed by a rotating disk electrode (RDE, 0.19 cm 2 ) and a rotating ring disk electrode (RRDE, with an annular area of ​​0.15 cm 2 , the disk area is 0.19 cm 2 ). The catalyst ink was prepared as follows: Co@mC (1 mg) was added as a conductive agent to a mixture of 0.95 mL of deionized water and 10 μL of Nafion solution. A uniform suspension was obtained by ultrasonic treatment for 0.5 h. A total of 25 μL of the as-synthesized catalyst solution was drop-casted on the surface of RDE or RRDE and dried in an oven at 38 °C for 1 h for H2O2 detection.

[0064] A platinum ring was used as the working electrode for the measurements. All potentials refer to the reversible hydrogen electrode (RHE). The measurement potentials from silver / silver chloride to the relatively reversible hydrogen electrode can be used using the following relationship:

[0065] E RHE =E Ag / AgCl +E 0 Ag / AgCl vs.SHE +0.059pH (1)

[0066] All tests were performed at room temperature. O2 was purged with 0.1 M KOH (pH = 13) electrolyte for at least 30 min, and the CV curve scan rate was 50 mV s -1 Linear sweep voltammetry (LSV) of ORR was collected by RRDE at 1600 rpm. The ring current was recorded by keeping the ring potential at 0.5 V vs. Ag / AgCl to detect the H2O2 produced at the disk electrode. Using the reversible [Fe(CN)6] 4- / [Fe(CN)6] 3- The system was used to determine the collection efficiency (N, 25%) of the RRDE electrode used.

[0067] The selectivity of the catalyst for H2O2 formation is calculated according to the following relationship

[0068]

[0069] The number of electrons (n) transferred at the disk electrode during oxygen reduction is calculated as follows

[0070]

[0071] The kinetic parameters were analyzed by the Kuteck-Levitch (KL) equation:

[0072]

[0073]

[0074] The collection yield of H2O2 is obtained by mixing with Ce(SO4)2(2Ce 4+ +H2O2→2Ce 3+ +2H + +O2) reaction to produce H2O2 concentration. The color of the solution changes from yellow to colorless. 4+ The concentration was determined by UV-Vis spectroscopy at 316 nm.

[0075] 1. Electrochemical performance of Co@mC composites

[0076] 1) 2e of Co@mC composites -ORR Performance

[0077] The 2e of a series of Co@mC composites was measured in an O2-saturated 0.1 M KOH solution. - ORR performance, among which Zn-MOF and Zn-MOF@Co 2+ Materials were also tested as controls. Figure 5 (a) shows that no obvious redox peak is obtained in the CV curve of Zn-MOF, indicating that its electrochemical activity is poor. 2+ and Co@mC-500, at 0.6V RHE Only an inconspicuous cathodic peak was observed at a potential of , which was attributed to the reduction of oxygen. 2+ In comparison, Co@mC-700 and Co@mC-900 catalysts have a RHE The larger cathodic peaks at - ORR activity. In addition, at 0.82V RHE There is also a cathode peak at 2+ / Co 3+ Co@mC-700 and Co@mC-900 have excellent 2e - The ORR capability may be related to the uniform dispersion of CoO nanoparticles on the carbon skeleton and the coordination environment that promotes a large amount of ORR activity. RHE About 0.73 mA cm -2 The current density is higher than that of Co@mC-900 (at 0.63V RHE 0.46 mA cm -2 ).

[0078] 2) ORR kinetics of Co@mC composites

[0079] Figure 5 (b) shows the ORR kinetics of the Co@mC composites probed using RRDE as the working electrode. Obviously, the onset potential of Co@mC-900 is lower than that of Co@mC-700. The onset potential of the Co@mC-900 catalyst is 0.85 V. RHE , tend to react via a two-electron reaction (O2+2H2O+2e - →OH2 - +OH - ,U0 O2 / OH2- =0.74V vs RHE). In addition, at 0.6V RHE At the set potential of , 0.19 cm 2The ORR current on the glassy carbon disk electrode was 1.72 mA, which was greater than that of Co@mC-700 (1.22 mA) and Co@mC-500 (0.93 mA). This indicates that the electrocatalytic ORR activity of Co@mC is positively correlated with the calcination temperature, which is attributed to the introduction of oxygen-containing groups and defects in the Zn-MOF-derived material as the oxygen content gradually increases. These introduced oxygen-containing groups and defects can serve as ORR active sites because they are more easily adsorbed by O2. In addition, the introduced C-OH acidic groups lead to a hydrophilic surface of the catalyst, promoting the diffusion of dissolved oxygen to the electrochemically active sites. The CV curves of Co@mC-900 were carried out in 0.1M KOH saturated with N2 or O2, respectively. Compared with the blank in N2-saturated solution, an obvious reduction current appeared in the CV curve of Co@mC-900 in O2-saturated solution, further suggesting the effect of 2e - The remarkable electrocatalytic activity for ORR.

[0080] In addition, in RRDE measurement, the ring current is generated by the H2O2 (or OOH - ) produced by oxidation (collection efficiency is 25%), which can represent 2e - Electrocatalytic activity of ORR. According to the polarization curve of the ring electrode ( Figure 5 (b)) The dashed line at 0.4V RHE The Co@mC-900 catalyst showed the highest cyclic current of 0.47 mA, which is higher than that of Zn-MOF@Co 2+ (0.21mA), Co@mC-500 (0.23mA) and Co@mC-700 (0.35mA). Therefore, 2e - The electrocatalytic activity of ORR for Co@mC can be improved by high temperature calcination, and the highest improvement can be achieved at a calcination temperature of 900° C. Considering environmental factors and synthetic condition limitations, 900° C. is the preferred temperature of the present invention.

[0081] 3) Faradaic selectivity of Co@mC composites for H2O2

[0082] The Faradaic selectivity for H2O2 (H2O2%) was further quantified by RRDE measurements. The ring potential was kept at 0.5 V relative to RHE, as Figure 5 (d) In contrast, the Co@mC-900 catalyst exhibited a relatively high H2O2 yield selectivity (over 90%) at 0-3V RHE The n value in the potential range is 2 to 2.12, which is higher than that of Zn-MOF and Zn-MOF@Co 2+As mentioned above, due to the well-dispersed CoO nanoparticles, the Co@mC-500 and Co@mC-700 catalysts also have higher H2O2 selectivity than the original MOF. As shown in the HAADF-STEM image ( Figure 4 (h) shows that the presence of some tiny CoO nanoparticles with a diameter of several nanometers in the Co@mC-900 catalyst may accelerate the breaking of the O-O bond and the formation of H2O2 during the reaction. These trends are consistent with the two-electron ORR process reported previously for metal oxide catalysts, where the H2O2 selectivity increases with decreasing metal oxide cluster size and the maximum selectivity is achieved on the catalyst with the highest nanoparticle dispersion.

[0083] 4) Catalytic activity of Co@mC composites for electrocatalytic synthesis of H2O2

[0084] The activity of the series of Co@mC catalysts was evaluated by measuring the kinetic current with the actual amount of catalyst, e.g. Figure 6 (a) Considering the changes in the limiting kinetic current of different ORR pathways, Co@mC-900 at 0.6V RHE The mass activity is 29.51 Ag -1 , higher than Co@mC-500(14.35Ag -1 ) and Co@mC-700(21.47Ag -1 The improvement in mass activity can be attributed to the highly dispersed CoO nanoparticles on the carbon skeleton in the Co@mC-900 catalyst. In addition, the Tafel slope of the Co@mC-900 catalyst (72 mV dec -1 ) is significantly lower than that of Co@mC-500 catalyst (108 mV dec -1 ) and Co@mC-700 catalyst (103mVdec -1 ),like Figure 6 In general, the high H2O2 selectivity and fast ORR kinetics of the Co@mC-900 catalyst make it an ideal candidate for the two-electron ORR process under alkaline conditions.

[0085] Figure 7 The ORR polarization curves of Co@mC-900 catalyst at different rotation speeds of 400-2025 rpm are given. According to the corresponding KL curve, the catalytic process of Co@mC-900 is mainly a two-electron pathway, in which a small part of the four-electron reaction is mixed. RHE The calculated n values ​​are in the range of 2.24–2.52 over the potential range of 2.5 Å, indicating that the main two-electron ORR pathway is caused by the CoO nanoparticles dispersed on the carbon skeleton and the adjacent sites lacking OO cleavage.

[0086] 5) Yield of H2O2 electrocatalytically synthesized by different amounts of Co@mC composite materials

[0087] To evaluate the effect of catalyst dosage on H2O2 yield, the catalysts at different dosages (13.1, 26.3, 39.4, 52.6, and 78.9 μg cm -3 ) RRDE curve of H2O2 yield of Co@mC-900 catalyst, such as Figure 8 The results show that in the range of 13.1 to 52.6 μg cm -3 In the voltage range of 0-0.5 V, when the catalyst dosage is 52.6 μg cm -3 When the ring current density of the catalyst is in the range of 0.3-0.54 mA·cm -2 , the catalyst's selectivity for H2O2 yield reaches 90%, such as Figure 8 (b) shows that the catalyst has more active sites. -3 When the ring current density of the catalyst is in the range of 0.22-0.36 mA·cm -2 The selective H2O2 yield of the catalyst reached 82%. The above results show that the optimal dosage of Co@mC-900 catalyst is about 52.6 μg cm -3 , showing high H2O2 selectivity in the range of 0-0.5 V. When the catalyst loading exceeds this critical value, the excess catalytic active sites that are not saturated by O2 flux may trigger side reactions at high overpotentials (4e - ORR, H2O2 reduction and / or decomposition), resulting in a decrease in H2O2 selectivity.

[0088] 6) Stability of Co@mC composite electrocatalytic synthesis of H2O2

[0089] Stability is 2e - Another key issue in the practical application of ORR electrocatalysts is the stability of the ORR performance of Co@mC-900 catalysts through cycle testing. Fig. 9 As shown in (a), after 5000 cycles of CV potential cycling, the CV curve remains almost unchanged. Fig. 9 As shown in (b), LSV test was performed after every 1000 cycles of CV test, and the results showed that the Co@mC-900 catalyst still reversed its activity to 2e - ORR, E 1 / 2 The value is only shifted by 5 mV. The current density at 0.6 V is 1.17 mA cm -2 , and only dropped by 15.8% after 5000 cycles.

[0090] In addition, if Fig.10 As shown in (a), the current of the ring electrode and disk electrode of the RRDE electrode based on the Co@mC-900 composite material remained stable for 10 h without obvious attenuation. Fig.10 As shown in (b), the current of the ring electrode of the RRDE electrode based on the Co@mC-900 composite material decreases slightly, which can be attributed to the gradual accumulation of H2O2 in the electrolyte; Fig.10 As shown in (c), the selectivity of the Co@mC-900 catalyst for catalytic synthesis of H2O2 in the voltage range of 0-0.6V is still as high as 83% or more after a 10h stability test. Fig.10 As shown in (d), the electron transfer number of the Co@mC-900 catalyst for catalytic synthesis of H2O2 is maintained at 1.96-2.10. The excellent structural stability and catalytic durability of the Co@mC-900 prepared by the present invention may be mainly attributed to the following factors: (i) the combination of Zn-MOF-derived layered carbon materials and CoO nanoparticles greatly promotes the catalytic performance, which also includes a small amount of carbon-nitrogen network that can promote the uniformly dispersed active sites to be fully exposed and react with O2 molecules; (ii) the layered structure of the formed Co@mC-900 can provide an intermediate transmission channel for electron transfer; (iii) the Zn-MOF@Co 2+ The Co@mC-900 catalyst obtained by high-temperature annealing brings a large number of defect sites while losing Zn and enhances structural stability.

[0091] 2. Application of Co@mC composites in practical devices

[0092] In addition, in order to explore the application of the prepared Co@mC-900 catalyst in actual devices, the H2O2 production was evaluated on carbon paper. A homemade electrochemical H-type electrolytic cell was used (the specific structure and construction method of the H-type electrolytic cell refer to: Xu Chaoquan, Preparation and Performance Research of Electrocatalyst for Synthesis of H2O2 Based on 2e-Oxygen Reduction, University of Electronic Science and Technology of China, 2022), the cathode was the electrode loaded with the catalyst, the anode was a platinum sheet, the reference electrode was Ag / AgCl, and the amount of the loaded catalyst was 0.1 mg cm -2 , ambient temperature was 25°C, quantified by cerium sulfate titration, and the yield of H2O2 was determined in 0.1 M KOH.

[0093] like Fig.11 As shown in Figure 2, in the potential range of 0.2 to 0.6 V, the yield of H2O2 over the Co@mC-900 catalyst at 0.6 V is approximately 684.4 mmol L -1 h -1 g cat -1. The results show that the Co@mC-900 prepared by the present invention has significant progressive catalytic activity, and its selectivity can reach 92.4% at a lower potential. In order to gain a deeper understanding of the advantages of the Co@mC-900 catalyst, its catalytic properties such as activity, selectivity and stability were compared with those of the benchmark catalyst (Table 1). In contrast, the H2O2 production produced by the Co@mC-900 catalyst of the present invention is higher than that of some SACs, Co-based catalysts or carbon-related catalysts, and is twice the amount of H2O2 produced by the Au-Pd catalyst in direct synthesis, which proves the feasibility of the Co@mC-900 composite material of the present invention as a catalyst for electrocatalytic production of H2O2.

[0094] Table 1 2e of different catalysts – ORR Performance Comparison

[0095]

[0096] References:

[0097] [1]Zhu J., Xiao

[0098] [2]Gao J., Yang Hb, Huang X., et al. Enabling direct H2O2 production inacidic media through rational design of transition metal single atom catalyst[J]. Chem, 2020, 6(3):658-674.

[0099] [3] Zhang C., Zhang J., Zhang J., et al. Tuning Coal into Graphene-LikeNanocarbon for Electrochemical H2O2 Production with Nearly 100% FaradayEfficiency [J]. ACS Sustain. Chem. Eng., 2021, 9(28): 9369-9375.

[0100] [4]Lenarda A.,Bevilacqua M.,Tavagnacco C.,et al.Selectiveelectrocatalytic H2O2 generation by cobalt@N-doped graphitic carbon core–shell nanohybrids[J].ChemSusChem,2019,12(8):1664-1672.

[0101] [5]Sun Y.,Li S.,Paul B.,et al.Highly efficient electrochemical production of hydrogen peroxide over nitrogen and phosphorus dual-doped carbon nanosheet in alkaline medium[J].J.Electroanal.Chem.,2021,896:115197.

[0102] [6]Xia F.,Li B.,Liu Y.,et al.Carbon free and noble metal freeNi2Mo6S8 electrocatalyst for selective electrosynthesis of H2O2[J].Adv.Funct.Mater.,2021,31(47):2104716.

[0103] [7]Li H.,Wen P.,Itanze DS,et al.Scalable neutral H2O2electrosynthesis by platinum diphosphide nanocrystals by regulating oxygen reduction reaction pathways[J].Nat.Commun.,2020,11(1):3928.

Claims

1. A Zn-MOF@Co 2+ A method for preparing a derivative material, characterized in that: The following steps are involved: 1) reacting a zinc source and an organic ligand in a solvent, separating the solid from the liquid, and drying the solid to obtain Zn-MOF; the organic ligand is curcumin; 2) Mix the cobalt salt and Zn-MOF in an organic solvent, separate the solid and the liquid, and dry the solid to obtain Zn-MOF@Co 2+ ; The cobalt salt is cobalt nitrate hexahydrate; the mass ratio of the Zn-MOF to the cobalt salt is 1:2; 3) Put Zn-MOF@Co 2+ Calcination at 500℃~900℃ under protective atmosphere to obtain Zn-MOF@Co 2+ Derivative material Co@mC.

2. Zn-MOF@Co according to claim 1 2+ A method for preparing a derivative material, characterized in that: In step 1), the zinc source is zinc acetate dihydrate; the mass ratio of the zinc source to the ligand is 6:10 to 12:

10.

3. Zn-MOF@Co according to claim 2 2+ A method for preparing a derivative material, characterized in that: The reaction in step 1) is first carried out at room temperature for 4 to 5 hours, and then heated to 60 to 90° C. for 48 to 96 hours.

4. Zn-MOF@Co according to any one of claims 1 to 3 2+ A method for preparing a derivative material, characterized in that: The solvent in step 1) is a mixed solvent of dimethylacetamide and anhydrous ethanol; the volume ratio of dimethylacetamide to anhydrous ethanol is 3:1 to 5:

1.

5. Zn-MOF@Co according to claim 1 2+ A method for preparing a derivative material, characterized in that: In step 2), the organic solvent is methanol; the mixing is to mix the methanol solution of Zn-MOF with the methanol solution of cobalt nitrate hexahydrate, wherein the content of Zn-MOF in the methanol solution of Zn-MOF is 5 mg mL -1 The content of cobalt nitrate hexahydrate in the methanol solution of cobalt nitrate hexahydrate is 10 mg mL -1 .

6. Zn-MOF@Co according to claim 1 2+ A method for preparing a derivative material, characterized in that: In step 2), the stirring is carried out at room temperature for 6 hours.

7. Zn-MOF@Co according to claim 1 2+ A method for preparing a derivative material, characterized in that: In step 3), the calcination temperature is 900°C.

8. Zn-MOF@Co according to claim 1 or 7 2+ A method for preparing a derivative material, characterized in that: In step 3), the calcination time is 2 hours.

9. A Zn-MOF@Co prepared by the preparation method according to any one of claims 1 to 8 2+ Application of the derived materials as catalysts for electrocatalytic synthesis of hydrogen peroxide.

Citation Information

Patent Citations

  • Zn-MOF (at) Ti < 3 > C < 2 > T < x > hybrid material as well as preparation method and application thereof

    CN114288406A